Trump, Brexit and the Transatlantic Relationship: The New Paradigms of the Trump Era - Laëtitia Langlois (Revue LISA)
On 27 January 2017 during a joint press conference with the British Prime Minister Theresa May at the White House, Donald Trump praised the vote in favour of Brexit as “a wonderful thing’ and a ‘blessing for the world.’” Brexit was a fantastic opportunity for him as the themes raised by pro-Brexiteers echoed his own “politics of anger”: hostility against the élites, rejection of lax immigration policies, indictment of the effects of free trade and globalisation, etc. Therefore, his support for Brexit and for its main spokesman Nigel Farage is no surprise except in so far as it stands in sharp contrast with his predecessors’ stance who all defended the idea of a United Kingdom fully committed to the European Union. Donald Trump is not a president to be bothered with history and tradition: the liberal world order and old European ties do not faze him in the least. His only guides when it comes to making decisions are his short-term political needs. Thus, studying Donald Trump’s position towards Brexit and more largely towards the European Union will reveal some constant themes: opportunism, populism and unpredicatility..